Unseen city : the majesty of pigeons, the discreet charm of snails & other wonders of the urban wilderness - Johnson, Nathanael (Rodale, 2016)
"Johnson argues that learning to see the world afresh, like a child, shifts the way we think about nature: Instead of something distant and abstract, nature becomes real all at once comical, annoying, and beautiful. This shift can add tremendous value to our lives, and it might just be the first step in saving the world...[C]hapter by chapter, "Unseen City" takes us on a journey that is part nature lesson and part love letter to the world's urban jungles. With the right perspective, a walk to the subway can be every bit as entrancing as a walk through a national park."--Provided by publisher.